(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Artificial Intelligence (AI) is becoming a key tool in education, automating the verification of students' calculations, which is especially important for disciplines involving mathematical and technical calculations. The article focuses on improving the digital literacy of students and teachers through the integration of innovative technologies. The use of AI transforms learning by promoting individualization of the process, instant feedback and in-depth mastering of the material. The perspectives of adaptive educational platforms that analyze the level of preparation of students and build personalized learning trajectories are discussed. The challenges of AI implementation are also discussed, including algorithm improvement, ethical issues of automated assessment, and integration with existing educational systems. The study evaluated the effectiveness of implementing AI systems to check students' calculation papers. The results showed that the use of artificial intelligence allowed to reduce the time of work verification by 60-70%, to increase the accuracy of assessment by 25-30% due to minimization of the human factor, and to increase student performance by 15-20% due to individualized recommendations. It is concluded that the use of artificial intelligence in the verification of calculations not only increases the efficiency of the educational process, but also develops students' skills in working with digital technologies, which are necessary in modern conditions. The introduction of artificial intelligence into the educational environment contributes to the creation of adaptive, interactive and innovative approaches to learning, improving the quality of education and its accessibility.